Heterobimetallic μ2-halocarbyne complexes. Issue 32 (27th July 2022) - Burt, Liam K.; Dewhurst, Rian D.; Hill, Anthony F.; Kong, Richard Y.; Nahon, Emily E.; Onn, Chee S.
Abstract : A range of heterobimetallic μ2 -halocarbyne complexes arise from the reactions of terminal halocarbyne complexes with gold(i ) and platinum(0) reagents. Abstract : The halocarbyne complexes [M(CX)(CO)2 (Tp*)] (M = Mo, W; X = Cl, Br; Tp* = hydrotris(dimethylpyrazolyl)borate) react with [AuCl(SMe2 )], [Pt(η 2 -H2 CCH2 )(PPh3 )2 ] or [Pt(η 2 -nbe)3 ] (nbe = norbornene) to furnish rare examples of μ2 -halocarbyne complexes [MAu(μ2 -CX)Cl(CO)2 (Tp*)], [MPt(μ2 -CCl)(CO)2 (PPh3 )2 (Tp*)] and [W2 Pt(μ2 -CCl)2 (CO)4 (Tp*)2 ]. The complex [WPt(μ2 -CCl)(CO)2 (PPh3 )2 (Tp*)] spontaneously rearranges to the μ2 -carbido complex [WPt(μ2 -C)Cl(CO)2 (PPh3 )2 (Tp*)] during silica-gel chromatography. One phosphine ligand of [WPt(μ2 -CCl)(CO)2 (PPh3 )2 (Tp*)] is readily substituted by CO to afford [WPt(μ2 -CCl)(CO)3 (PPh3 )(Tp*)]. These μ2 -halocarbyne complexes have been interrogated by spectroscopic, crystallographic and computational methods, the latter by reference to data for terminal halocarbyne precursors [M(CX)(CO)2 (Tp*)].